Analisis motivasi siswa dalam mengikuti ekstrakurikuler bola voli - Septiawan, Gilang; Nasution, Nana Suryana; Sumarsono, Rhama Nurwansyah (Jurnal Porkes, 2023)
This research aims to analyze how much student motivation there is and wants to examine how much intrinsic motivation and extrinsic motivation students have in participating in volleyball extracurricular activities at MAN 3 Karawang. Quantitative descriptive research uses survey methods, with data collection techniques using instruments in the form of questionnaires. The population and sample in this study were 32 students. The instrument used was a questionnaire consisting of 35 questions. Data analysis used descriptive statistical analysis with respondents' achievement levels. The results of the research show that students' overall motivation for participating in volleyball extracurriculars can be categorized as moderate with the respondent's achievement level being 79.69%. Meanwhile, the intrinsic motivation factor obtained a respondent achievement level of 84.59% in the high category and the extrinsic motivation factor obtained a respondent achievement level of 74.79% in the medium category. The overall conclusion is categorized as moderate